(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
Emily Dickinson, a prolific American poet of the 19th century, is known for her unique style and profound exploration of themes such as love, nature, and death. While she is often categorized as a pre-modernist poet, her work also exhibits strong elements of Romanticism, a literary movement that emphasized emotion, imagination, and the beauty of nature. This article delves into how Dickinson expressed Romantic motifs in her poetry. “A Bird came down the Walk” and “Hope is the thing with feathers” are analyzed in order to represent the main features of romanticism in her work.